Assessment of iron status among adolescents in the fishing villages of Tuaran, Sabah - Foo, Leng Huat (2002)
Iron deficiency anaemia is the most common micronutrient deficiency in the world affecting the general health of millions. In Malaysia, a moderately high prevalence of anemia is often reported in infants, young children and women of childbearing age. Data on anaemia is scant for the adolescents. This study was undertaken to assess the iron status of adolescents from six fishing villages in Tuaran, Sabah. A total of 199 subjects comprising 94 male and i 05 female were included in the study. Their ages ranged from 12 to 19 years with a mean of 15.2 years. Multiple iron status indicators namely, serum ferritin (SF), transferrin saturation (TS), mean corpuscular volume (MeV) and hemoglobin concentration were used to estimate the stages of iron deficiency. The majority of the male (68.1 %) and female subjects (82.9%) had normal body mass index (BMI) values, while 25.5% and 14.3% of the males and females respectively were underweight. A small percentage of the adolescents was overweight, that is 6.4% and 2.9% of the male and female respectively. Male adolescents showed significantly higher mean values for hemoglobin concentration, hematocrit, red blood count, serum iron, transferrin saturation and serum ferritin than the female subjects. In contrast, female adolescents had a significantly higher level of total iron binding capacity.